Gullo’s syndrome – what do we know? - Rycyk, Anna; Furtak, Paulina; Mądro, Agnieszka; Kasztelan-Szczerbińska, Beata; Cichoż-Lach, Halina (Gastroenterology Review/Przegląd Gastroenterologiczny, 2021)
Benign pancreatic hyperenzymemia (Gullo’s syndrome) is characterized by a more than threefold increase of the serum pancreatic enzymes lipase and amylase activity in the absence of any pancreatic disease. Recently, there is an increase in describing cases of Gullo’s syndrome in medical literature. Gullo’s syndrome is a diagnosis of exclusion, and clinicians should be aware of various other conditions which can cause elevation of pancreatic enzymes. However, the diagnostic pathway should be done with the right accuracy to avoid unnecessary examinations.